Humidifier Inhalation of Lavender Flower to Reduce Anxiety of Pre-mastectomy Patients: Humidifier Inhalation of Lavender Flower to Reduce Anxiety of Pre-mastectomy Patients - Sihaloho, Sri Bungaria; Simanullang, Rostime Hermayerni (LLDIKTI Wilayah 1, 2024)
Introduction: breast cancer is the cause of the highest fertility in women and continues to breast cancer has not existed until now. When faced with a couple breakup, it is common to experience disappointment. by using the Wilcoxon signed rank test. Objective: to analyze the influence of lavender flower aromatherapy; humidifier on the anxious scale of pre-mastectomy patients. Method: pre-experimental design with one group pre and post-test without control. Before the treatment, the patient's anxiety level is first controlled, then given inhalation of lavender flowers through a humedifier with 15 drops of lavender oil in 150 ml of water and evaporated for 15 minutes. Then the patient's anxiety level is measured again. The data were analyzed using the Wilcoxon signed range test. Result: using Wilcoxon signed range test analysis recorded with p-value 0.001 (<0.05). Conclusion: there is a significant effect of inhalation of lavender flower humidifier to reduce anxiety levels of pre-masctectomy patients. Suggestions, the results of this study can be done where all pre-mastectomy patients, first given inhalation of lavender flower humidifier and should be done research for other types of preoperative surgery.